2021
DOI: 10.1525/elementa.2020.00113
|View full text |Cite
|
Sign up to set email alerts
|

DMS emissions from the Arctic marginal ice zone

Abstract: Phytoplankton blooms in the Arctic marginal ice zone (MIZ) can be prolific dimethylsulfide (DMS) producers, thereby influencing regional aerosol formation and cloud radiative forcing. Here we describe the distribution of DMS and its precursor dimethylsulfoniopropionate (DMSP) across the Baffin Bay receding ice edge in early summer 2016. Overall, DMS and total DMSP (DMSPt) increased towards warmer waters of Atlantic origin concurrently with more advanced ice-melt and bloom stages. Relatively high DMS and DMSPt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 164 publications
(245 reference statements)
6
13
0
Order By: Relevance
“…Previously reported DMS levels in polar oceans varied between 3 to 18 nM (Mungall et al, 2016;Jarníková et al, 2018;Uhlig et al, 2019), with up to 74 nM in the sub-surface Chl a maximum of the Baffin Bay (Galí et al, 2021). Hence, these are overall in the same range as our values.…”
Section: Dms and Meshsupporting
confidence: 84%
“…Previously reported DMS levels in polar oceans varied between 3 to 18 nM (Mungall et al, 2016;Jarníková et al, 2018;Uhlig et al, 2019), with up to 74 nM in the sub-surface Chl a maximum of the Baffin Bay (Galí et al, 2021). Hence, these are overall in the same range as our values.…”
Section: Dms and Meshsupporting
confidence: 84%
“…A total of 24 depth profiles were measured during this deployment. In the marginal ice zone in summer and spring, the sea ice cover controls the biogeochemistry and the physical structure of the water column, including the distribution of Chl a and density (48) as well as bacterial activity (49). Thus, exactly as in Wohl et al (50), vertical profiles were classified by sea ice cover (SIC) at the time of sampling (Figure 3).…”
Section: Depth Profilesmentioning
confidence: 99%
“…In addition, both seasonal and decadal observations showed that enhanced Atlantification led to an increase in the summertime proportion of Phaeocystis pouchetii and decrease of diatoms (Nöthig et al, 2015;Orkney et al, 2020;Reigstad et al, 2002). Phaeocystis is likely one of major contributors to dimethylated sulfur compounds at high latitudes (Galí et al, 2021). Therefore, the close link between major DMSP-producing phytoplankton and saline Atlantic waters may partly explain why the SSS is a key influencing factor of the spatiotemporal variations of DMS in the Arctic region.…”
Section: Relationships Between Dms and Environmental Factorsmentioning
confidence: 99%
“…Therefore, the close link between major DMSP-producing phytoplankton and saline Atlantic waters may partly explain why the SSS is a key influencing factor of the spatiotemporal variations of DMS in the Arctic region. It should be noted that salinity change and water stratification caused by sea-ice melt may also affect phytoplankton biomass and community structure (Ardyna and Arrigo, 2020;Galí et al, 2021), but the specific influence of sea-ice melt on DMS remains to be studied. Our results show that the coastal and Arctic regions belong to bloom-forced regime for DMS cycling, which is consistent with previous statements (Toole and Siegel, 2004).…”
Section: Relationships Between Dms and Environmental Factorsmentioning
confidence: 99%